Vibrational characteristics of shape memory alloy-embedded 3D woven composite plate - Baitab, Danish Mahmood; Majid, Dayang Laila; Abdullah, Ermira Junita; Hamid, Mohd Faisal Abdul (Springer, 2023)
Introduction: Investigation of vibrational characteristics is important in the design of a structure for dynamic loading conditions. Objectives: This research explains a comprehensive method of experimentally investigating modal properties of a shape memory alloy (SMA)-embedded 3D woven composite plate. Methods: The SMA wire is embedded in three different 3D orthogonal interlock structures. Dynamic properties, such as the natural frequencies and the mode shapes, are obtained through the roving impact hammer method and the contribution of SMA and its positioning for improving modal properties is assessed. Also, the effect of binding yarns of different 3D configurations on modal properties is studied. Results: SMA wire imparts a significant effect on dynamic properties as SMA at the center has given higher bending mode frequencies upon activation while the torsional mode frequencies are more affected when the SMA wire is embedded off-center. The binding yarns of 3D structures also play an important role in affecting dynamic properties as layer-to-layer interlocked structure shows higher increments in natural frequencies while the modified structure having strong interlocking of binding yarns with SMA wire has given the lower percentage increments as restricting SMA to contract upon activation. Conclusion: Hence, the vibrational characteristics of SMA-embedded 3D woven composite plates are significantly affected by activating SMA wire depending upon the position of the SMA wire as well the 3D structure that holds the SMA wire.